Eating Disorders: Innovative Directions in Research and Practice.
DOI: 10.1037/10403-011
|View full text |Cite
|
Sign up to set email alerts
|

Body image dissatisfaction as a motivator for healthy lifestyle change: Is some distress beneficial?

Abstract: Body image dissatisfaction is pervasive and steadily increasing (Cash & Henry, 1995), with a majority of people reporting dissatisfaction with weight or body shape. The research literature focuses on not only the "disturbed" aspects of body image (e.g., body image disturbance evidenced by patients with eating disorder or those with body dysmorphic disorder) but also the "normative" aspects of appearance-based body image (e.g., dissatisfaction seen in nonpsychiatric populations; . Clearly delineating where norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
2
2

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 44 publications
4
81
2
2
Order By: Relevance
“…When perceived image differs from the ideal image there can be varied levels of distress. Very low body image distress or concern may evoke either little or no motivation to change body weight, while those with very high body image distress are more likely to use unhealthy weight-correction methods (42,43) . Our data do indicate, however, that boys are less likely to want to be thinner than they currently are.…”
Section: Discussionmentioning
confidence: 99%
“…When perceived image differs from the ideal image there can be varied levels of distress. Very low body image distress or concern may evoke either little or no motivation to change body weight, while those with very high body image distress are more likely to use unhealthy weight-correction methods (42,43) . Our data do indicate, however, that boys are less likely to want to be thinner than they currently are.…”
Section: Discussionmentioning
confidence: 99%
“…7 For instance, a metaanalytic review reported that overall greater LTPA participation was associated with a better body image. 8 However, some individual studies have shown that greater LTPA is associated with worse body image because people use physical activity to manage body image dissatisfaction.…”
mentioning
confidence: 99%
“…8 However, some individual studies have shown that greater LTPA is associated with worse body image because people use physical activity to manage body image dissatisfaction. 7 These conflicting findings are reflected in Cash's biopsychosocial model of body image, 9 which identifies a relationship between the use of self-regulatory behaviors (for example, LTPA and dieting) and body image, and suggests that the variables can moderate the direction of this relationship. The primary purpose of our study was to examine the relation-ship between LTPA and body image among men with SCI, and whether the perceived impact of body image on QOL moderates this relationship.…”
mentioning
confidence: 99%
“…In much of the literature, weight concerns have been discussed as a risk factor for adverse health outcomes, yet recently some investigators have proposed that weight concerns may also motivate healthpromoting behaviors. 13 In the current issue of The Journal, Robinson et al 14 report important new data that speak to these three issues. Specifically, they examined body dissatisfaction and overweight concerns in a large, ethnically diverse, schoolbased sample of third-grade boys and girls.…”
Section: See Related Article P 181mentioning
confidence: 99%
“…In light of the reported adverse effects of body dissatisfaction and dieting in terms of risk for depression and eating disorders, it may be perceived as heretical to ask whether body dissatisfaction may also have a positive side. Heinberg et al 13 have raised the question of whether body dissatisfaction may motivate efforts to practice healthful eating, and a recent study by Neumark-Sztainer et al 22 suggests that not all "dieting" is problematic. Obesity experts and eating disorder experts need to work together to develop recommendations to the public about strategies to reduce obesity, body dissatisfaction, and weight concerns among our youth without contributing further to the very problem those strategies are intended to solve.…”
Section: See Related Article P 181mentioning
confidence: 99%